1989
DOI: 10.1021/jm00131a004
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity, biotinyl, and iodo analogs as probes for vasotocin receptors

Abstract: Vasotocin (AVT) analogues with tyrosine or phenylalanine in position 9, i.e., [9-tyrosine]AVT, [2-phenylalanine,-9-tyrosine]AVT, and 1-desamino[9-(p-aminophenylalanine)]AVT, were synthesized by the solid-phase method. These compounds showed a high biological activity in the hydroosmotic toad bladder assay. Using the chemically reactive functional groups on tyrosine and p-aminophenylalanine in position 9, we prepared iodinated, photoreactive, and affinity ligands, i.e., [2-phenylalanine,9-(iodotyrosine)]AVT, 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In contrast, the photolabeling method allows covalent labeling of the receptors that have firstly bound the photoprobe. The corresponding molecules can be easily synthesized by introducing a commercial photoactivatable reagent on previously described ligands (Boer and Fahrenholz, 1985;Buku et al, 1989). However, this solution is rarely efficient since the structural modification often results in a strong decrease of the ligand affinity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the photolabeling method allows covalent labeling of the receptors that have firstly bound the photoprobe. The corresponding molecules can be easily synthesized by introducing a commercial photoactivatable reagent on previously described ligands (Boer and Fahrenholz, 1985;Buku et al, 1989). However, this solution is rarely efficient since the structural modification often results in a strong decrease of the ligand affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we synthesized PhAcAL(Btn)VP as a specific biotinylated probe for V,, re-ceptors. A biotinylated agonist has been reported for the toad bladder vasotocin receptor (Buku et al, 1989) and Jans et al (1990) synthesized derivatives of [deamino-2,4-diaminobu-tyrate4, Arg'IVP with biotin attached at position 4. These peptides were shown to be agonists and exhibited similar affinity for V,, and V, VPR (Jans et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The availability of a biotinylated hormone analogue allows the investigator to exploit the very high affinity interaction of biotin with avidin in a variety of immunocytochemical applications (reviewed by Wilchek and Bayer, 1988). Previous investigations have demonstrated that biotinylated analogues of [Arg'IVP and vasotocin, both agonists (Buku et al, 1989;Jans et al, 1990) and an antagonist (Howl et al, 1991a), can bind to neurohypophyseal peptide hormone receptors whilst simultaneously coupling to avidin or its conjugates. An obvious requirement in such studies is that the biotinylated ligand should retain high affinity for its receptor.…”
mentioning
confidence: 99%
“…The success of this approach is critically dependent upon the ability of the biotinyl-substituted hormone ligand to bind simultaneously to both avidin and the receptor. For example, the hydro-osmotic activity of biotinylated analogues of vasotocin was reversed following the addition of avidin [14]. However, the spacer arms of the molecules used in this study were very short.…”
Section: Discussionmentioning
confidence: 94%